Nog steeds geslote eredienste? Deel 2 - Wyk, I. W. C. van (Hervormde teologiese studies, 1994)
Should church services still be closed? Part 2 This paper - in two parts - deals with the question of whether the Nede duitsch Hervormde Church should continue being a church for white pe sons only. The auther argues that this practice is not according to bibl cal teachings and, at the same time, that it will be unwise to continue under the future sociopolitical circumstances in South Africa. He there fore calls on the Nederduitsch Hervormde Church to abandon this practice as it will bring the church into conflict with its own theological tradition